2013
DOI: 10.1016/j.cplett.2013.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Optical switching of radical pair conformation enhances magnetic sensitivity

Abstract: Graphical abstract

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
61
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(62 citation statements)
references
References 37 publications
1
61
0
Order By: Relevance
“…In particular, given the discussion of the previous Section, how can one do better in a chemically realistic way? Towards addressing this question we will (i) take advantage of a very promising approach of optically switching the conformation of the radical-pair, recently proposed in [45], and (ii) include a realistic exchange interaction in the Hamiltonian, which changes (a) the initial spin state before the radicalpair commences its magnetometric state evolution, and (b) the effective measurement basis before it recombines.…”
Section: Quantum Reaction Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, given the discussion of the previous Section, how can one do better in a chemically realistic way? Towards addressing this question we will (i) take advantage of a very promising approach of optically switching the conformation of the radical-pair, recently proposed in [45], and (ii) include a realistic exchange interaction in the Hamiltonian, which changes (a) the initial spin state before the radicalpair commences its magnetometric state evolution, and (b) the effective measurement basis before it recombines.…”
Section: Quantum Reaction Controlmentioning
confidence: 99%
“…In summary, given the maximally anisotropic coupling that resulted from the optimization of Section V.C, the . 3. According to the proposal of [45], radical-pair reactions can be controlled by binding the two radicals to the two ends of a molecular switch, the conformation of which can be laser controlled. We here consider that apart from the Zeeman and hyperfine coupling term in the magnetic Hamiltonian, in the cis conformation there is also a finite exchange coupling, which the authors in [45] take to be infinite.…”
Section: Quantum Reaction Controlmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite all of the theoretical arguments, the ultimate goal of studying the mechanisms of bird navigation is to learn from nature and to design highly effective devices that can mimic biological systems to detect weak magnetic fields, and to use the geomagnetic field to navigate. Previous literature has shown that the anisotropic hyperfine coupling plays a crucial role in the magnetic field sensitivity of the avian compass and has provided routes towards the design of biologically inspired magnetic compass sensors . Scientists have exploited many practical methods to realize a device based on the avian chemical compass.…”
Section: Chemical Compass In Birdsmentioning
confidence: 99%
“…Other studies have achieved to map nanomagnetic field using a radical pair reaction and found a method to improve the magnetic sensitivity of chemical magnetometers …”
Section: Chemical Compass In Birdsmentioning
confidence: 99%